Java EE 6 pocket guide - Gupta, Arun (Technical evangelist) (O'Reilly Media, 2012)
This handy guide provides an overview of Java Enterprise Edition 6's main technologies and includes extensive, easy-to-understand code samples that demonstrate the platform's many improvements. You'll quickly understand how Java EE 6 simplifies the process of developing and deploying web and enterprise applications. Explore what's new in Java EE 6, including Contexts and Dependency Injection and the Java API for RESTful Web Services Discover how Java EE 6 features relate to design patterns in web and enterprise applications Get the specifications for making your application Java EE compliant Learn about revisions to Enterprise JavaBeans, JavaServer Faces, and other components Find out how Java EE 6 profiles change the platform's?one size fits all? approach Get started with Java EE 6 development and deployment, using NetBeans IDE and GlassFish.